Factors Influencing Mortgage Foreclosure of Commercial Banks in Ibadan, Nigeria - Sikiru, O. A.; Adewale, R. A. (International Journal of Real Estate, 2025)
Mortgage foreclosure is a recovery tactic used by financial institutions especially in developing nations where institutional, legal, and economic issues frequently make it less successful and pose a threat to commercial banks’ financial stability. This study examined factors influencing mortgage foreclosure of commercial banks in Ibadan, Nigeria and this was with a view to providing information that could enhance best lending practice. The study adopted survey method by administering questionnaire on the credit, account and loan officers of commercial banks in Ibadan using total enumeration of the 19 commercial banks operating in the study area and the data were analyzed using mean ranking and principal factor analysis. The study found that loan types, industry characteristics, prepackaged bankruptcy, traditional bankruptcy and out-of-court restructurings and macroeconomic conditions were the most prominent factors influencing mortgage foreclosure with mean scores of 4.067, 4.00, 4.00 and 4.00 respectively using 5-point Likert scale. The least factors influencing foreclosure were loan size and loss of job with mean values of 3.000 and 2.867 respectively. Through principal component analysis, four (4) factors were extracted and accounted for 78.598% of total variance explained. The study recommends the promoting ethical lending practices is essential, with regulatory bodies ensuring that banks adhere to standards that minimize conflicts of interest and ensure fair treatment of borrowers throughout the loan lifecycle and attention to the factors influencing foreclosure during loan application and assessment before disbursement will go a long way of mitigating the likelihood of default leading to foreclosure. Also Enhanced monitoring systems and rigorous client selection processes are vital for identifying high-risk borrowers early on, allowing banks to implement supportive measures that encourage repayment and reduce the likelihood of foreclosure.